2020
DOI: 10.2147/ppa.s268395
|View full text |Cite
|
Sign up to set email alerts
|

<p>Level of Adherence and Associated Factors Among HIV-Infected Patients on Antiretroviral Therapy in Northern Ethiopia: Retrospective Analysis</p>

Abstract: Background: Poor adherence to ART increases viremia, which leads to disease progression and transmission of drug-resistant HIV strains. This study aimed to assess the level of ART adherence and associated factors among adolescents and adult patients enrolled in ART care in Northern Ethiopia. Methods: A retrospective analysis was conducted among 19,525 patients from April 2015 to March 2019. Data verification and filtration were done in Excel 2013 before exporting to STATA 14.0. Ordinal logistic regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Although it has been documented that the best response to ART is seen when adherence is 100% [ 16 ], however, with the advent of new drugs such as the integrase strand transfer inhibitors and newer protease inhibitors, adherence with these drugs do not necessarily need to be 100% as the drugs could provide undetectable viral loads even with lower levels of adherence [ 38 – 40 ]. Nevertheless, the efficacy and durability of ART drug regimens still requires near perfect adherence rates as high as 95% or more [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been documented that the best response to ART is seen when adherence is 100% [ 16 ], however, with the advent of new drugs such as the integrase strand transfer inhibitors and newer protease inhibitors, adherence with these drugs do not necessarily need to be 100% as the drugs could provide undetectable viral loads even with lower levels of adherence [ 38 – 40 ]. Nevertheless, the efficacy and durability of ART drug regimens still requires near perfect adherence rates as high as 95% or more [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, baseline HIV stage is statistically associated significantly with adherence to ART in which patients with baseline HIV stage I was more likely to be adherent (AOR: 2.194 95% CI: 1.116, 4.314) as compared with patients with baseline HIV stage IV. This is similar to a retrospective study done in northern Ethiopia in which those patients with HIV stage II(AHR: 0.47 95% CI: 0.36, 0.60), WHO stage III (AHR: 0.25 95% CI: 0.19, 0.34), and WHO stage IV (AHR: 0.57 95% CI: 0.41, 0.81) had a lower risk to be adherent to the prescribed HIV medicine as compared with HIV stage I [ 13 ]. This may be due to the effect of serious opportunistic infections developed in the advanced stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…While risk factors as lower socioeconomic status, diagnosed in the earlier years are consistent with our study, female gender was not significant and age over 50 (compared than 40 - 49), was associated with MPR over 90% in our study. Regarding age and adherence, there have been discrepancies between studies and this may be associated with different target populations and categorization of age groups [ 24 ]. However, there were previous studies that reported reasons for poor adherence among young people as denial and fear of HIV infection, low self-esteem, and unstructured and chaotic lifestyles [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%